Effect of chronic Trypanosoma brucei infection on the course of louping ill virus infection in mice. - Reid, H W (1979)
The course of louping-ill virus infection in mice chronically infected with Trypanosoma brucei was investigated. The mean survival time of mice infected with virus alone was 10.2 days, compared to 12.8 days in mice infected with T. brucei 14 days before virus challenge, and the cumulative mortality in the two groups was 62.5 and 90%, respectively. Virus was only inconsistently detected in the blood of mice given virus alone but was regularly present at high titers for up to 12 days in the blood of mice previously infected with T. brucei. Titers of virus in brains were also higher in dually infected mice, and encephalitis was of greater severity. These results indicate that the immunosuppressive effect of chronic trypanosomiasis may markedly increase susceptibility to acute virus infection. In addition, it is concluded that vector-vertebrate relationships of arthropod-transmitted viruses may be altered by concurrent trypanosome infection.